Editorial. Issue 2 (13th April 2023) - Doyle, Denise
Virtual Creativity 12.2 brings together an eclectic range of research and practice from the community including computationality and play, embodying evil and the inner world of women's bodies. Also in this issue is a review of the Venice Biennale 2022 curated by Cecilia Alemani, who highlights that, for the first time in its 127-year history, the Biennale includes a majority women or gender non-conforming artists. The issue concludes with an interview with Brazilian artist Raphael Arar who works at the nexus of complex systems, transdisciplinary design and arts-based research.